Comparison of HeLa 229 and McCoy cell cultures for detection of Chlamydia trachomatis in clinical specimens. - Thewessen, E A (1989)
Consecutive clinical specimens of Chlamydia trachomatis (1,048) were inoculated in parallel on DEAE-dextran- and cycloheximide-treated HeLa 229 cells and cycloheximide-treated McCoy cells. HeLa 229 cell culture detected 113 positive specimens, and McCoy cell culture detected 103 positive specimens. This difference is not significant. However, HeLa 229 cell culture yielded significantly more inclusions than McCoy cell culture in the 95 specimens positive in both cell types (P = 0.042). For routine diagnostic purposes, a choice for one of the cell types may be determined by local preferences.